2014
DOI: 10.1186/s40550-014-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157:H7 in Raw Meat in Addis Ababa, Ethiopia: Prevalence at an Abattoir and Retailers and Antimicrobial Susceptibility

Abstract: Background: Although raw meat and its products are commonly consumed in traditional Ethiopian diets, E. coli O157: H7 is rarely studied compared to other countries. Thus the present study has been designed to determine the prevalence and assess the antimicrobial susceptibility of E. coli O157: H7 isolated from beef, sheep meat and goat meat at one abattoir and in 48 selected raw meat retail shops in Addis Ababa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
60
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 22 publications
24
60
7
1
Order By: Relevance
“…This is in agreement with the report of Mude et al (2017), who showed 92.3% of isolates were multidrug resistant. Moreover, various authors (Bekele et al 2014;Iweriebor et al 2015;Atnafie et al 2017) from the country and abroad reported multidrug resistance patterns. Moreover, the present study revealed that the prevalence of multidrug resistant isolates was higher in milk and milk products (28.4%) as compared to meat (15.4%) samples.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the report of Mude et al (2017), who showed 92.3% of isolates were multidrug resistant. Moreover, various authors (Bekele et al 2014;Iweriebor et al 2015;Atnafie et al 2017) from the country and abroad reported multidrug resistance patterns. Moreover, the present study revealed that the prevalence of multidrug resistant isolates was higher in milk and milk products (28.4%) as compared to meat (15.4%) samples.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in a very short period of time, antibiotic resistance will appear. High prevalence of resistance against chloramphenicol in the E. coli O157:H7 strains of meat samples have been reported from Iran [10,22], USA [33], Turkey [28], UK [34] and Nigeria [35]. High differences of the prevalence of antibiotic resistance in the E. coli O157:H7 strains in different studies is due to the fact that maybe availability of antibiotics, their cost and even idea of veterinarian for antibiotic prescription are different in each region.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the highest prevalence rate was found in beef (13.32%), pork (6.90%), chicken (3.28%) and duck (2.54%). Bekele et al (2014) [28] reported that of 384 meat samples collected from Addis Ababa, 39 (10.2%) were positive to E. coli O157:H7. They reported that beef (13.30%), sheep (9.40%) and goat (7.80%) meat samples had the highest prevalence of E. coli O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…have been implicated in foodborne outbreaks (Kilic et al, 2007;Adzitey et al, 2011Adzitey et al, , 2012aAdzitey et al, , 2013Adzitey et al, , 2014Islam et al, 2011;Bekele et al, 2014;CDC., 2014b;Carnot et al, 2014). Adzitey et al (2014) identified Escherichia coli in beef sold in the Yendi Municipality of Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Adzitey et al (2014) identified Escherichia coli in beef sold in the Yendi Municipality of Ghana. The prevalence of Escherichia coli O157:H7 in beef samples in Addis Ababa, Ethiopia was 13.3% (17/128) (Bekele et al, 2014). In USA, CDC.…”
Section: Introductionmentioning
confidence: 99%